2018
DOI: 10.3390/ijms19092747
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of HIV Infection, AIDS, and Antiretroviral Therapy to Exocrine Pathogenesis in Salivary and Lacrimal Glands

Abstract: The structure and function of exocrine glands are negatively affected by human immunodeficiency virus (HIV) infection and its co-morbidities, including innate and adaptive immune responses. At the same time, exocrine function may also be influenced by pharmacotherapies directed at the infectious agents. Here, we briefly review the role of the salivary glands and lacrimal glands in normal physiology and exocrine pathogenesis within the context of HIV infection and acquired immune deficiency syndrome (AIDS), inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 169 publications
1
21
0
1
Order By: Relevance
“…Most MiSGs contain mucus acini and secrete mucus saliva, which creates a protective lubricating micron-thick film that helps to avoid the subjective feeling of dry mouth [ 82 , 83 ]. Additionally, MiSGs produce saliva during sleep and therefore a decreased MiSG flow rate due to HIV/SIV induced inflammation may partially explain the night time dry mouth reported by HIV patients [ 84 , 85 , 86 ]. Although MiSGs contribute less than 10% of the saliva volume [ 82 , 83 ], they secrete high concentrations of immunoglobulin A that protects the oral mucosa from bacterial invasion [ 82 , 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most MiSGs contain mucus acini and secrete mucus saliva, which creates a protective lubricating micron-thick film that helps to avoid the subjective feeling of dry mouth [ 82 , 83 ]. Additionally, MiSGs produce saliva during sleep and therefore a decreased MiSG flow rate due to HIV/SIV induced inflammation may partially explain the night time dry mouth reported by HIV patients [ 84 , 85 , 86 ]. Although MiSGs contribute less than 10% of the saliva volume [ 82 , 83 ], they secrete high concentrations of immunoglobulin A that protects the oral mucosa from bacterial invasion [ 82 , 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study showed that Fusobacterium , Campylobacter , Prevotella , Capnocytophaga , Selenomonas , Actinomyces , Granulicatella , and Atopobium were increased in HIV-infected individuals after receiving ART, while Aggregatibacter was significantly decreased. [ 45 ] Another study collected samples from 35 HIV-infected subjects at baseline and after 24 weeks of ART to compare the differences in oral microbiota. The results showed that the dominant phyla in samples from patients with 24 weeks of ART remained similar to those observed at baseline, and the diversity was not significantly different between samples collected at baseline and those collected after 24 weeks of ART.…”
Section: Effects Of Potential Interventions On the Oral Microbiomementioning
confidence: 99%
“…Oral microbiome turns to opportunistic pathogens that can lead to oral manifestations closely related to HIV/AIDS, such as oral candidiasis (OC) [3,6], oral hairy leukoplakia (OHL) [7,8], linear gingival erythema (LGE) [4,9], necrotizing ulcerative gingivitis (NUG), and necrotizing ulcerative periodontitis (NUP) [10]. In addition, through the HIV/AIDS onset, the use of antiretroviral therapy (ART) and psychological stress can trigger xerostomia in PLWHA [11,12]. Among other oral manifestations in HIV/AIDS patients, the most common is OC [3].…”
Section: Oral Innate Immunity In People Live With Hiv/aidsmentioning
confidence: 99%